SANGGIT DAN GARAP LAKON BANJARAN PERTUNJUKAN WAYANG KULIT PURWA GAYA SURAKARTA - , Sugeng Nugroho; , Prof. Dr. Timbul Haryono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to address four problems related to the sanggit and garap of banjaran stories in classical Surakarta style shadow puppet theatre (pakeliran purwa), including: (1) why banjaran stories have appeared in Javanese shadow puppet theatre